2015
DOI: 10.3109/08977194.2015.1125349
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 attenuates renal tubular injury by decreasing oxidative stress and inflammation in streptozotocin-induced diabetic mice

Abstract: In this study, we aimed to research the restorative effects of exendin-4, a GLP-1 analog, on renal tubular injury in streptozotocin-induced diabetes model. BALB/c male mice were divided into four groups: non-diabetic, non-diabetic + exendin-4 (3 μg/kg), diabetic and diabetic + exendin-4. In our diabetic model, we observed renal injury mainly in tubular area rather than glomeruli and exendin-4 decreased tubular injury with its glucose lowering effect. Besides, PCNA positive tubular cells, activities of LDH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…We were able to show that exendin-4 reduces Na + K + ATPase activity, suggesting reduced CSF secretion at the choroid plexus. Previous studies have shown similar effects of exendin-4 on Na + K + ATPase activity in the renal system (34). In kidney proximal tubule epithelial cells and pancreatic b cells, GLP-1 modulates Na + concentration through increased cAMP and PKA activation (18,35).…”
Section: Discussionmentioning
confidence: 61%
“…We were able to show that exendin-4 reduces Na + K + ATPase activity, suggesting reduced CSF secretion at the choroid plexus. Previous studies have shown similar effects of exendin-4 on Na + K + ATPase activity in the renal system (34). In kidney proximal tubule epithelial cells and pancreatic b cells, GLP-1 modulates Na + concentration through increased cAMP and PKA activation (18,35).…”
Section: Discussionmentioning
confidence: 61%
“…Old studies in diabetes models evaluated the NKA activity in the whole kidney and nephron segments, but not in isolated PTs [147], and were inconclusive. Results of recent studies in the whole kidney are still contradictory [148][149][150][151][152][153][154] probably because of mixed tissue responses and discrepancies in disease duration and glucose levels.…”
Section: Glucose Effects On Renal Glucosementioning
confidence: 99%
“…Ophthalmic Res 2020;63:404-412 DOI: 10.1159/000504891 causes RPE cell dysfunction or apoptosis. GLP-1 receptor agonist can inhibit oxidative stress in some cells, such as pancreatic β cells, myotube, and renal cells [18][19][20]. However, there is no evidence on whether EX4 can reduce oxidative stress-induced RPE cell damage.…”
Section: Discussionmentioning
confidence: 99%